The Implementation of Critical Thinking in Teaching and Learning Speaking to Students at Madrasah Aliyah Muhammadiyah Limbung - Nuryati; Ratna Dewi; Sitti Asriati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The research aimed to investigate how the teacher implements critical thinking in teaching English speaking at Madrasah Aliyah Muhammadiyah Limbung. This study was designed as qualitative research. The study involved one English teacher and sixteen students at eleventh grade at Madrasah Aliyah Muhammadiyah Limbung. The Data were collected through observation sheet that used lesson plan for observing what the teacher does in class, interview conducted directly (offline interview) with the teacher, and teacher’s document refers to the lesson plan used in teaching Speaking through critical thinking. The results were analyzed using data reduction, data display, and conclusion. Then, reference Facione's (2007) critical thinking used in the analysis. This study found that the teacher implements critical thinking in teaching English speaking through the Problem-Based Learning (PBL) model with various activities such as discussions and presentations. This method encourages students to think critically and understand cause-and-effect relationships in various contexts and the teacher help students through discussions and exercises. In conclusion, the implementation of critical thinking in teaching and learning speaking had a positive impact on “students' understanding” of cause-effect relationships and their speaking skills.